SYNTHESIS, ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITIES OF ETHYL 2-(2-CYANO-3- (SUBSTITUTED PHENYL)ACRYLAMIDO)-4,5-DIMETHYLTHIOPHENE-3-CARBOXYLATES - K, Madhavi; G, Sree Ramya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Objective of the study was to synthesize and evaluate a series of novel compounds, ethyl 2-(2-cyano-3-(substituted phenyl)acrylamido)- 4,5-dimethylthiophene-3-carboxylates, for in vitro antioxidant and in vivo anti-inflammatory activities. Methods: Ethyl 2-(2-cyano-3-(substituted phenyl)acrylamido)-4,5-dimethylthiophene-3-carboxylates were synthesized by knoevenagel condensation of active methylene group of ethyl 2-(2-cyanoacetamido)-4,5-dimethylthiophene-3-carboxylate with substituted benzaldehydes. The synthesized compounds were evaluated for their in vitro antioxidant properties in three different models, viz., reduction of 1,1-diphenyl-2-pycrylhydrazyl free radical, scavenging of nitric oxide free radical, and ferric ion-induced lipid peroxidation using rat brain homogenate. Few selected compounds with good antioxidant properties were pharmacologically evaluated for anti-inflammatory activity by carrageenan-induced rat paw edema model. Results: Clean and efficient synthetic procedure was used for the preparation of series of compounds. The structures of synthesized compounds were confirmed by infrared, 1H nuclear magnetic resonance and mass spectra. The antioxidant activity data revealed that the compounds of ethyl 2-(2-cyano-3-(substituted phenyl)acrylamido)-4,5-dimethylthiophene-3-carboxylate containing phenolic substitution showed greater antioxidant activity. Hence, the active compounds were evaluated for anti-inflammatory activity and found to possess good activity. The percentage inhibition of rat paw edema obtained for the evaluated compounds was in the range of 70.2-83.1, comparable to the standard drug diclofenac (85.0%). Conclusion: The use of inexpensive, eco-friendly and readily available reagents, easy work-up and high purity of products makes the procedure a convenient and robust method for the synthesis of title compounds. The compounds of ethyl 2-(2-cyano-3-(substituted phenyl)acrylamido)-4,5- dimethylthiophene-3-carboxylate containing phenolic substitution showed greater antioxidant and anti-inflammatory activities.